Saving versus deleting thoughts affects focal and lateral attitude change (Guardar vs. eliminar los pensamientos influye en los cambios actitudinales focales y laterals). Issue 2 (4th May 2021) - Bohner, Gerd; Boege, Ronja M. J.; Glaser, Tina; Klempel, Lea; Linne, Roman
ABSTRACT: Thought handling may affect the subsequent use of thoughts in evaluative judgements. Thus, a person's attitudes are more influenced by thoughts about the attitude object when the person has saved (versus deleted) a representation of these thoughts. We examined if thought handling would affect not only focal attitude change but also lateral attitude change. Students ( N = 200) listed positive thoughts about a focal object and later either saved or deleted a representation of their thoughts. Then their explicit and implicit attitudes towards the focal object, a lateral (= related) object and an unrelated object were assessed. Results showed that explicit focal attitudes were affected more by thoughts in the save conditions than in the delete conditions. These effects generalized to explicit lateral attitudes but not to explicit unrelated attitudes. Thought (handling) effects on implicit attitudes were generally weak. We discuss the results in terms of a self-validation approach and the lateral attitude change model.